Development of an integrated multi-objective approach to formulate optimal harvesting policies with the aim of sustainable management of groundwater resources: study area: Varamin Plain. Issue 2 (3rd March 2023) - Azizi, Hamid reza; Azizi, Hamed
Abstract: In the present study, an integrated multi-objective simulation -optimization model was developed using a NSGA-II optimization algorithm and GMS simulation software with the aim of sustainable harvesting from the Varamin aquifer. For this purpose, the quantitative model of the aquifer was simulated. Based on the calibrated model and integrated with the optimization algorithm, a two-objective management model was developed to control the exponential drop in the groundwater level and ensure sustainable harvesting from the wells. Then, according to multi-criteria decision-making methods and the Borda aggregation method, the optimal harvesting scenario of wells in operation was analyzed. The results show that more than 69% of the wells in the study area have experienced a rise of up to 30 m in the groundwater level during a 1-year period. It indicates the relative improvement of the aquifer in the direction of restoring its saturated thickness. Also, the comparison of the results obtained from the optimal and existing conditions showed that by applying the proposed model, an average of 46.9% can be saved in the harvesting of groundwater resources. For this purpose, it is necessary to reduce the allowed amount of harvesting from wells in this area from 21 to 11 L/s. HIGHLIGHTS: Optimal multi-objective management of underground water resources with a simulation–optimization model. Choosing the optimal groundwater extraction scenario by combining MCDMs. Evaluation of the spatial changes in the aquifer level under the scenario of optimal withdrawal from exploitation wells. Graphical Abstract